Crystal structures and characterizations of (nitrato-O) (nitrato-O,O′)(η6-hexamethylbenzene)ruthenium(II) and di(trifluoroacetato-O)(H2O-O)(η6-hexamethylbenzene) ruthenium(II) - Lu, X.L. (2014)
10.1080/15533170500360164